A cross sectional study to assess the effectiveness of orientation and induction programme among public health officers of a municipal corporation in North India: pre-test and post-test analysis - Gupta, Sujata; Taneja, Neha; Nidhi, Karuna (International Journal Of Community Medicine And Public Health, 2022)
Background: Vector borne diseases like malaria & dengue are of public concern. Public Health Officers have the job to identify and investigate health issues among people. But there is a need for induction training and re-training for ensuring adequate awareness and safe practices in health care settings. The present study was conducted to study the effect of orientation trainings on the knowledge of public health officers about the common vector borne diseases like malaria and dengue. Methods: This was a cross-sectional study conducted among 22 public health officers of Municipal Corporation of North India. Pre-test and post-test questionnaire was asked related to topics such as vector borne diseases, their prevention, treatment and water related diseases. Posttest was asked after two days of induction and orientation training. The pre- and post-test scores were tabulated and statistically analyzed using statistical package for the social sciences (SPSS) version 21. Data was presented in descriptive form and statistical significance of difference (taken as p-value <0.05) was calculated using paired t test. Results: The present study reported that the orientation programme conducted was highly informative to the medical officers. Study showed that post-test response was higher as compared with pre-test response and this difference was found statistically significant (p<0.002). Conclusions: Informative trainings are helpful to increase knowledge and giving information about the recent changes in the health programme to public medical officer who are particularly working in the community setting.